PENGEMBANGAN MEDIA BROSUR MATEMATIKA DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS II PADA MATERI BANGUN DATAR SDN 48 LEPUNG BERUANG TAHUN AJARAN 2024/2025 - Wati, Cici Anggrena; Rayo, Kandida Maro; Aristo, Thomas Joni Verawanto (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to develop a mathematics brochure to enhance students’ learning interest in the topic of plane shapes. The research employed the ADDIE development model, with data collection instruments including questionnaires, interviews, and documentation. The development stage involved validation by media and content experts, yielding high feasibility scores of 84.25% and 91.66%, respectively. Implementation was conducted through small group trials with 10 students at SDN 20 SP.2 SKPH Manis Raya and large group trials with 48 students at SDN 48 Lepung Beruang. Student responses to the mathematics brochure were categorized as “very good,” with average percentages of 85.89% for the small group, 90.77% for class II A, and 88.76% for class II B. Effectiveness was measured using the N-Gain test, showing a significant increase in learning interest: 74.49% (“moderately effective”) for the small group, 85.15% (“highly effective”) for class II A, and 87.70% (“highly effective”) for class II B. These results indicate that the mathematics brochure is a highly feasible and effective medium to improve students’ interest in learning plane shapes.